Re-Membering Methodology in Theologies of Disability - Barton, Sarah Jean (Journal of disability & religion, 2022)
Writing out of the togetherness of life with his son Adam Brock, Brian Brock’s Wondrously Wounded: Theology, Disability, and the Body of Christ offers a unique theological methodology that embodies both theoretical argument and Christian praxis. This article traces the methodological landscape of the field of disability theology, illustrating how Brock’s approach both embodies and promotes a praxis that re-members those with and without disabilities in the life of Christian discipleship. Comparing Brock’s method with other theologians who embrace inclusive research methods to investigate disability, as well as responding to critiques of Brock’s methodological approach in Wondrously Wounded, this article examines how Brock resists an “atrophied pneumatology” that creatively challenges the field of theological reflection on disability. Wondrously Wounded embraces a methodology that not only makes normative suggestions for Christian ethical praxis but enacts a praxis reflective of the disability rights maxim “nothing about us without us” throughout the research process itself.